Nanoscale 3D Printing of Quantum Dots on Paper. Issue 9 (28th May 2021) - Bae, Jongcheon; Kim, Seonghyeon; Ahn, Jinhyuck; Sim, Ho Hyung; Wajahat, Muhammad; Kim, Jung Hyun; Yoon, Seog-Young; Kim, Ji Tae; Seol, Seung Kwon; Pyo, Jaeyeon
Abstract : Nanoscale integration is difficult on rough surfaces despite their ubiquity and usefulness. Paper is an emerging material system because it is renewable, flexible, and lightweight. However, owing to the rough surface of paper, it is difficult to use conventional nanoscale integration methods. Herein, nanoscale printing of CdSe/ZnS quantum dots on paper using a 3D printing method with surface adaptive control of the femtoliter meniscus is demonstrated. The approach allows the direct integration of light‐emitting materials on the intact surface of paper with nanoscale lateral confinement. The 3D‐printed nanostructures can be treated as a planar pattern of the nanoscale dots when viewed from the top. The individually addressable nature of the 3D printing method enables the equalization of the printed heights, which is essential for practical use in general planar systems. This method can be used in many areas that require paper such as paper electronics, security printing, biomedical engineering, and possibly other material systems with rough surfaces. Abstract : Nanoscale printing of quantum dots on the rough surface of paper is demonstrated. The 3D printing approach allows the direct integration of light‐emitting materials on the intact surface of a copy paper at the nanoscale resolution. This method can be used for high‐density integration in paper electronics or, more generally, structural electronics.